2014
DOI: 10.18632/oncotarget.1633
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin (NTS) and its receptor (NTSR1) causes EGFR, HER2 and HER3 over-expression and their autocrine/paracrine activation in lung tumors, confirming responsiveness to erlotinib

Abstract: Alterations in the signaling pathways of epidermal growth factor receptors (HERs) are associated with tumor aggressiveness. Neurotensin (NTS) and its high affinity receptor (NTSR1) are up regulated in 60% of lung cancers. In a previous clinical study, NTSR1 overexpression was shown to predict a poor prognosis for 5 year overall survival in a selected population of stage I lung adenocarcinomas treated by surgery alone. In a second study, shown here, the frequent and high expression of NTSR1 was correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Western blots were processed as previously described [33]. Western blots were revealed with antibodies directed against EGFR, ERK1/2, Thr202/Tyr204 pERK, PKB, Ser473 p-PKB (Cell Signalling Technology ® ), Tyr1173 p-EGFR, actin (Santa Cruz Biotechnology ® ).…”
Section: Western Blotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blots were processed as previously described [33]. Western blots were revealed with antibodies directed against EGFR, ERK1/2, Thr202/Tyr204 pERK, PKB, Ser473 p-PKB (Cell Signalling Technology ® ), Tyr1173 p-EGFR, actin (Santa Cruz Biotechnology ® ).…”
Section: Western Blotsmentioning
confidence: 99%
“…In addition, it was shown that the sustained stimulation Abbreviation: NTS, neurotensin; NTSR1, neurotensin receptor 1; HCC, hepatocellular carcinoma; HBV, hepatitis B virus; HCV, hepatitis C virus; EGF, epidermal growth factor; EGFR, epidermal growth factor receptor; ERK, extracellular signalregulated kinases; PKB, protein kinase B; VEGF, vascular endothelial growth factor; VEGFR, vascular endothelial growth factor receptor; PDGFR, platelet-derived growth factor receptor; RT-PCR, reverse transcriptase-polymerase reaction; OS, overall survival. 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 of NTSR1 generated autocrine regulation of epidermal growth factor receptors, producing cell hyper-sensitivity to tyrosine kinase inhibitors, as is the case for erlotinib in lung cancer or lapatinib in breast cancer [6,33]. NTS is expressed in the fetal human liver but repressed in the normal adult liver.…”
Section: Introductionmentioning
confidence: 99%
“…The recruitment of G protein was described through NTSR1 activation in microdomains (Heakal et al, 2011). In other cell types, cell proliferation, migration and invasion are depending on a transactivation of EGFR by NTSR1 (Amorino et al, 2007;Moody et al, 2014 ) or act through the increase of expression and activation of EGFR, HER2, HER3 (Younes et al, 2014;Dupouy et al, 2014).…”
Section: Functionmentioning
confidence: 99%
“…Its functions in oncogenesis depend on EGFR, HER2 and HER3 expression in breast cancer cells (Dupouy et al, 2014).…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation